Analysis of the Frequency and Detectability of Objects Resembling Nuclear/Radiological Threats in Commercial Cargo. Issue 2 (2nd September 2019) - Henderson, Brian S.
Abstract: The detection of smuggled nuclear/radiological materials or weapons in commercial cargo remains a severe technical challenge due to the complexity of the global cargo network, sources of normally occurring radiation, and the broad nature of the threat. This article presents an analysis of the physical constraints on the nature and detectability of nuclear and radiological threats, using 122, 500 radiography images from a containerized cargo stream. This analysis suggests that existing radiography systems, in conjunction with passive monitoring, may offer stronger detection capabilities than previously realized and presents data on the distribution of material in stream-of-commerce cargo to inform the development of future technologies.